IMPACT OF HIV INFECTION AND TUBERCULOSIS ON THE PERIPHERAL BLOOD T-CELL DIFFERENTIATION - E. V. Vasileva (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
Tuberculosis is the leading cause of death among HIV infected individuals. In this regard, an important task is the timely detection of tuberculosis in HIV infected patients. Previously, we have shown that the diagnostic value of in vitro test, QuantiFERON-TB Gold In-Tube is not decreased in patients with HIV infection against the background of tuberculosis. However, it remains unclear what kind of cell populations produce IFNγ in response to specific Mycobacterium tuberculosis antigens stimulation in vitro, because the immunodeficiency, caused by HIV, makes primarily for a decrease the abundance and attenuation functions of CD4 T-lymphocytes. The aim of thшы work was to compare the degree of differentiation of T-lymphocytes CD4 (Th) and CD8 (Tcyt) in patients with pulmonary tuberculosis and healthy donors against the background of HIV infection. The study data were obtained during the examination of 28 patients with pulmonary tuberculosis without HIV infection (HIV–TB+), 23 patients with HIV infection (TB–HIV+) and 30 patients coinfected with HIV and tuberculosis (TB+HIV+). The comparison group consisted of 37 healthy individuals (TB–HIV–). Аbsolute and abundance (relative content) of major subpopulations of T-lymphocytes (based on the expression of CD27 marker, CD28, CD45RA and CD62L) in the peripheral blood for all patients included in the study (n = 118) were evaluated by flow cytometry approach. For patients with pulmonary tuberculosis (n = 58) QuantiFERON-TB Gold In Tube (Qiagen, QFT) test was performed. Th/Tcyt ratio was not significantly different among the groups of TB–HIV– and TB+HIV– (1.76 [1.51; 2.30] against 1.86 [1.22; 2.79], p = 0.960). At that time, the size of both subpopulations “terminally differentiated” Tcyt (Tcyt Eff, CD27–CD28– CD62L–CD45RA–) Th lymphocytes and effector memory lymphocytes (Th EM, CD27–CD28+CD62L–CD45RA–), was significantly different in all four study groups. Multidirectional changes of the absolute and abundance (relative content) in these cell populations in comparison with healthy donors for tuberculosis and HIV infection was noticed. Absolute content of Tcyt Eff, compared with healthy donors (76.1 [20.7; 143.5]), 4-fold increases in the group of HIV+TB+ and 2 times in groups TB+HIV– and TB–HIV+. Th EM content increases only at TB+HIV– group compare to healthy donors. In groups of patients with HIV infection (TB–HIV+ and TB+HIV+) a decrease in the content of these cells was observed. Thus, our work shows that the population of Th EM and Tcyt Eff could potentially be viewed as universal biomarkers for two socially significant infectious diseases: tuberculosis and HIV infection. In future experiments, it is necessary to validate these results to ensure specificity and determine the number of Th EM and Tcyt Eff specificly induced by Mtb antigens.